A practical protocol for correlative confocal fluorescence and transmission electron microscopy characterization of extracellular vesicles - Juan M. Martínez-Andrade; Daniel Salgado-Bautista; Kendra Ramirez-Acosta; Ruben Darío Cadena-Nava; Meritxell Riquelme (Microbiology Spectrum, 2025)
ABSTRACT Extracellular vesicles (EVs) have gained considerable attention in fungal biology research. However, imaging these membrane-bound particles presents challenges due to their nanoscopic size (typically <200 nm), which exceeds the resolution limit of conventional diffraction-limited laser scanning confocal microscopy (LSCM). While high-resolution techniques like transmission electron microscopy (TEM) offer superior spatial resolution, they are time-consuming, require specialized expertise, and are prone to artifacts that can interfere with accurate results. In this study, we propose a rapid method for confirming the vesicular nature of EVs using a correlative light and electron microscopy (CLEM) approach. EVs were isolated from culture filtrates of the model filamentous fungus Neurospora crassa, and their membranes were stained with the fluorogenic styryl dye FM1-43 for analysis. Fluorescent microspheres were used as fiducial markers alongside the stained EVs during sample preparation. Samples were first examined using LSCM, followed by negative staining with OsO4 vapors or uranyl acetate. The same regions observed with LSCM were subsequently analyzed with TEM. CLEM analysis revealed that vesicle-like structures with membranous features, as observed under TEM, corresponded to the dispersed green fluorescence signal seen with LSCM. These findings validate CLEM as a reliable method to examine the presence of EVs. This method can be implemented easily in labs that do not have access to a core facility with sophisticated multimodal microscopes. Furthermore, this method can be extended to study other structures, such as secretory vesicles, viral particles, protein nanoparticles, and polymeric nanoparticles.IMPORTANCEThis study presents an efficient and cost-effective correlative light and electron microscopy workflow for imaging nanosized extracellular vesicles (EVs) and other biological samples. The methodology involves sequential imaging using laser scanning confocal microscopy (LSCM) followed by transmission electron microscopy (TEM), enabling comprehensive characterization of EVs. This protocol uses fluorescence microscopy dyes to stain EV membranes and OsO4 vapors for negative or positive staining in TEM. This approach provides a reliable, versatile tool for studying nanoscale biological structures, with broad applications in cellular biology, nanomedicine, and related research fields.